The moderating role of kindness on the relation between trust and happiness - Jasielska, Dorota (Current Psychology, 2020)
A number of studies show that trust enhances both national and individual happiness. However, the mechanism underlying this association remains unclear. The aim of this study was to investigate the role of kindness in explaining the link between trust and happiness. Specifically, it was hypothesized that the more people believe that they have done for others, the stronger is the link between trust and happiness. Ninety-one students participated in a trust game and then completed measures assessing levels of happiness, trust, and kindness. Results revealed that level of happiness was related to the frequency of acts of kindness and the level of trust showed in a trust game. This finding suggests that while trust alone is associated with happiness, being kind strengthens this relationship. It seems that without prosocial activity people may not derive much happiness from being trusting. Possible explanations for the effects obtained and limitations of the study are discussed.